Introduction: The present study aimed to investigate the effect of social networks on sport participation approach among female students in Isfahan University of Medical Sciences, Isfahan, Iran. Materials and Methods: This correlation-causal study was don - Melika Iravani; Rasool Nazari (Vesnu Publications, 2020)
-